2021
DOI: 10.3389/fbioe.2021.793302
|View full text |Cite
|
Sign up to set email alerts
|

Swimming Phase-Based Performance Evaluation Using a Single IMU in Main Swimming Techniques

Abstract: Comprehensive monitoring of performance is essential for swimmers and swimming coaches to optimize the training. Regardless of the swimming technique, the swimmer passes various swimming phases from wall to wall, including a dive into the water or wall push-off, then glide and strokes preparation and finally, swimming up to the turn. The coach focuses on improving the performance of the swimmer in each of these phases. The purpose of this study was to assess the potential of using a sacrum-worn inertial measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Histograms of the changes in the goal metrics are displayed in Figure 3 . The root mean squared error ( RMSE ) for the estimation of each goal metric is extracted from our previous study ( Hamidi Rad et al, 2021a ) and shown specifically for each goal metric in vertical red lines in Figure 3 . The delta values lying inside the range of RMSE (± RMSE range) are too small to be valid as they might happen due the model errors and should be removed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Histograms of the changes in the goal metrics are displayed in Figure 3 . The root mean squared error ( RMSE ) for the estimation of each goal metric is extracted from our previous study ( Hamidi Rad et al, 2021a ) and shown specifically for each goal metric in vertical red lines in Figure 3 . The delta values lying inside the range of RMSE (± RMSE range) are too small to be valid as they might happen due the model errors and should be removed.…”
Section: Resultsmentioning
confidence: 99%
“…For technical reasons, only front crawl technique is examined here. However, based on our previous research ( Hamidi Rad et al, 2021a ), similar goal metrics can be extracted from other main swimming techniques (backstroke, butterfly, and breaststroke) to perform the same study. The lap time was recorded using stopwatch which is prone to human error and using more precise measurement methods such as cameras can increase the quality of this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, several studies reported in the literature have supported coaches in comprehensive monitoring of the performance of their athletes to develop and refine a training model. For example, in [15] numerous kinematic variables related to propulsion, posture, efficiency, and duration/rate of motion in four main swimming phases (wall push-off, glide, stroke preparation, and swimming) were extracted from an IMU attached to the sacrum. An IMU worn on the wrist or the upper-back was used to discriminate among the different swimming styles in [16,17], whereas in [18] the type of stroke and wall push-offs were detected by deriving pitch and roll angles from an accelerometer mounted on the swimmer's goggles.…”
Section: Introductionmentioning
confidence: 99%